1989
DOI: 10.2337/diab.38.12.1636
|View full text |Cite
|
Sign up to set email alerts
|

Association of IDDM and Attenuated Response of 2′,5′-Oligoadenylate Synthetase to Yellow Fever Vaccine

Abstract: Basal and yellow fever vaccination-induced 2',5'-oligoadenylate synthetase (2',5'A) activity was determined in blood mononuclear cells (peripheral blood lymphocytes [PBLs]) from insulin-dependent diabetes mellitus (IDDM) and matched control subjects. The live attenuated yellow fever vaccine represented a primary stimulus in all subjects. First, basal 2',5'A activity increased severalfold in response to yellow fever vaccination. In IDDM subjects, this increase was significantly lower (P = .025). Second, the 2',… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Therefore, it can be produced spontaneously by cells but be undetectable in plasma, which may explain the results obtained for 3 patients in this study (IFNa mRNA positive, IFN-a-protein negative). The results of our experiments provide direct evidence for the activation of the IFN-a system and can explain that IFN-dependent 2 ,5 oligoadenylate synthetase activity was high in the blood lymphocytes of patients with IDDM in studies by Bonnevie-Nielsen et al [22,23].…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, it can be produced spontaneously by cells but be undetectable in plasma, which may explain the results obtained for 3 patients in this study (IFNa mRNA positive, IFN-a-protein negative). The results of our experiments provide direct evidence for the activation of the IFN-a system and can explain that IFN-dependent 2 ,5 oligoadenylate synthetase activity was high in the blood lymphocytes of patients with IDDM in studies by Bonnevie-Nielsen et al [22,23].…”
Section: Discussionmentioning
confidence: 77%
“…We have also reported that the frequencies of genotypes carrying the genetic variant associated with elevated activity were significantly higher in individuals with type 1 diabetes than in nondiabetic control subjects [14]. Thus, our original findings of persistently elevated 2′5′AS activity in type 1 diabetes patients compared to controls [12, 13] were at least partly genetically determined. In other words, elevated 2′5′AS activity might be due to both genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 71%
“…Recently we have described a new splice variant, adding a new enzyme isoform to this family: OAS1-p52 [11]. We have suggested that processes within the antiviral 2′5′AS system might contribute to the etiopathogenesis of type 1 diabetes [12]. In several independent studies, we observed significantly increased 2′5′AS activity in patients with type 1 diabetes compared to healthy controls [12, 13].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Levels of this enzyme are increased in lymphocytes by day 4 postvaccination and reach a maximum at day 7. This enzyme catalyzes the production of 2Ј-5Ј oligoadenylates, which activates latent RNAase, which degrades viral mRNA and impairs cellular protein synthesis ( Bonnevie-Nielsen et al, 1989. Natural killer cells have also been shown to play a role early in virus infection ( Fagraeus et al, 1982 ).…”
Section: Innate Immune Responsementioning
confidence: 99%